2013
DOI: 10.1371/journal.pone.0074479
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide Variation in an Introgression Line of Rice-Zizania Revealed by Whole-Genome re-Sequencing

Abstract: BackgroundHybridization between genetically diverged organisms is known as an important avenue that drives plant genome evolution. The possible outcomes of hybridization would be the occurrences of genetic instabilities in the resultant hybrids. It remained under-investigated however whether pollination by alien pollens of a closely related but sexually "incompatible" species could evoke genomic changes and to what extent it may result in phenotypic novelties in the derived progenies.Methodology/Principal Find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 66 publications
1
29
1
Order By: Relevance
“…Moreover, the mutations were not only present in the 14 specific bands, but also in the remaining genome. Wang et al (2013) hybridized Zizania with rice and obtained a stability variant line (RZ35). Using whole genome sequencing, they found that there were a large number of nucleotide mutations in RZ35 (Wang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, the mutations were not only present in the 14 specific bands, but also in the remaining genome. Wang et al (2013) hybridized Zizania with rice and obtained a stability variant line (RZ35). Using whole genome sequencing, they found that there were a large number of nucleotide mutations in RZ35 (Wang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (2013) hybridized Zizania with rice and obtained a stability variant line (RZ35). Using whole genome sequencing, they found that there were a large number of nucleotide mutations in RZ35 (Wang et al, 2013). These results are consistent with our experiments and demonstrate that wide crosses and exogenous DNA can induce biological mutation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations